A novel reliability analysis approach for component‐based software based on the complex network theory. (3rd July 2018) - Li, Kewen; Yu, Mingxiao; Liu, Lu; Zhai, Jiannan; Liu, Wenying
Summary: Traditional software reliability evaluation approaches lack the analysis of intercomponent interactions of component‐based software systems, necessitating software reliability evaluation based on the reliabilities of the overall architecture and each component. In this paper, we propose a reliability evaluation model and an importance assessment technique for component‐based software based on the complex network theory. The components of a software system are identified and divided into 2 categories, input/output components and ordinary components. Then, the impact factors of ordinary components and input/output components are calculated based on the complex network theory and execution probabilities, respectively. Finally, the impact factors are used to evaluate the reliability of the software system and assess the importance of each component. Experimental results show that the proposed approach is able to estimate the reliability of component‐based software and provide relative priorities of the components that can be used to guide the system reliability optimization. Abstract : In this paper, a reliability evaluation model and an importance assessment technique for component‐based software based on the complex network theory are proposed. The components of a software system are identified and divided into two categories, input or output components and ordinary components to calculate the impact factors of components. The impact factors are used to evaluate the reliability of the software system and assess the importance of each component.